Gender inequality in the culinary profession in tourism from the perspective of university students with working experiences in culinary - Türkmendağ, Tuba; Karaman, Nilgün (Frontiers in Sociology, 2024)
Gender inequality is a phenomenon that is particularly prevalent in the culinary profession and professional culinary within the tourism sector, especially affecting female employees.The current study is approached in the context of the patriarchal societal structure and the unique characteristics of gender in the labor market in Turkey. In this regard, this study focuses on the views and opinions regarding gender inequality of undergraduate students in gastronomy and culinary arts programs and, associate degree in vocational cooking programs who have previously worked and/or interned in the professional culinary within the tourism sector in Turkey. For this purpose, a quantitative research method has been employed in the study. In order to reveal detailed insights into participants' evaluations, open-ended questions have also been included in the survey form. The quantitative findings from the study emphasized the importance of issues such as "the approach of managers", "working hours", and "promotion pathways" among the situations that cause gender inequality. The importance of "an equal and fair approach to employees", and "being kind and considerate to staff" were highlighted as essential qualities for being a good leader/head chef. Important factors in supporting the career of female chefs were identified as "equal pay for equal work", and "ensuring job safety". Findings obtained from open-ended questions have revealed that female employees are more exposed to gender inequality in the profession. In this context, issues such as "unequal pay, promotion, and working conditions", "harassment", "lack of recognition for female employees in the professional culinary", and "the effects of patriarchal norms" were highlighted. The study contains important findings that can contribute to increasing the representation of female employees in professional culinary within the tourism sector, improving the productivity and competitiveness of businesses, and addressing gender inequality in society.